WHATSAPP : THE POPULAR APPLICATION USED BY TEACHER AND STUDENTS FOR LONG DISTANCE LEARNING (It’s EFFECTIVENESS AND OPINION BY USER) - SITI ANIDA MAGHFIRA (STIT DARUL ULUM KOTABARU, 2021)
In early 2020 the world was busy with the emergence of the corona virus (Covid-19), including Indonesia. Covid-19 began to spread in Indonesia in March 2020. This made the government take a policy to limit the activities of all Indonesian people in various fields of life, including in education field. This policy makes the learning process that previously used the face-to-face method turned into a non-face-to-face method or better known as online learning. Online learning uses a variety of applications, one of which is widely used is the WhatsApp application. This research focus for investigating the effectiveness of whatsapp application and the opinion from its users. This research used mix methods between quantitative research and qualitative research. The data has been taken from the data which are collected in school that has been selected by researcher. For investigating the effectiveness of whatssapp, the researcher used quasi experimental method. There are two classes, One class was control group while another one was an experimental group. The data collection involved number of instruments, they are, written test to measure students writing achievement, and documentary to know the number of students. Pretest and posttest gave to the students to know the distinctions of their writing skill before and after treatment. Besides that, the posttest used to measure the validity and the reliability of the test by using Pearson Product Moment of SPSS 20. Besides, the qualitative research used interview, observation and documentation. The result of this research showed that the whatssapp application is effective in learning proces. Users opinions showed that students and teacher happy using this application and students having increased skill.